2021
DOI: 10.51594/ijmer.v3i7.245
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influence on Customer Purchase Intention via Livetream: Case of Vietnam

Abstract: The main purpose of this study is to propose and empirically test a conceptual model that clarifies shopping behavior via livestream on Facebook platform of people in Hanoi. The data was collected from at least 240 random Facebook users. The analysis results show that Facebook users tend to buy goods via livestream when they feel that the product quality, design, and product policy are convincing enough for them. In addition, there are other factors that also influence purchasing decisions, such as technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Furthermore, the reference group also impacted social influence, reflecting consumers' perceptions of online shopping decisions (Lin, 2007). This is supported by research by Tran (2021), who showed that the opinion of the reference group had a positive influence on the purchase intention of consumers via live streaming.…”
Section: Social Influencementioning
confidence: 69%
See 3 more Smart Citations
“…Furthermore, the reference group also impacted social influence, reflecting consumers' perceptions of online shopping decisions (Lin, 2007). This is supported by research by Tran (2021), who showed that the opinion of the reference group had a positive influence on the purchase intention of consumers via live streaming.…”
Section: Social Influencementioning
confidence: 69%
“…The combination of subjective consumer attitudes and extrinsic factors determines the purchase intention of consumers, and these factors should be studied to understand what is important to consumers when making purchase decisions (Guo et al, 2021). This research aims to study the factors influencing the purchase intention of consumers via live streaming in Malaysia, as there is a lack of studies on this topic in the country (Lakhan et al, 2021;Tran, 2021;(Sun et al, 2019;Zhou et al, 2021) and which will help fill the gap in Malaysia.…”
Section: Literature Review -Live Streaming Shoppingmentioning
confidence: 99%
See 2 more Smart Citations
“…Tại Việt Nam, mặc dù các sàn thương mại điện tử như Shopee, Lazada hay Tiki đã sử dụng rộng rãi tính năng PTT, những nghiên cứu về mặt lý thuyết và thực nghiệm về chủ đề này còn khá hiếm, đặc biệt là nghiên cứu về những nhân tố tác động đến ý định mua hàng qua PPT trên sàn thương mại điện tử của NTD. Những nghiên cứu về PPT tại Việt Nam cũng chủ yếu được thực hiện đối với các sản phẩm nói chung trên nền tảng mạng xã hội Facebook (Do và Vo, 2021;Tran, 2021). Bên cạnh đó, sự dịch chuyển cộng nghệ 4.0 và tác động của đại dịch COVID-19 cũng tạo điều kiện cho sự phát triển mô hình bán hàng qua PTT trong ngành bán lẻ nói chung và ngành thời trang, giày dép nói riêng.…”
Section: Giới Thiệuunclassified